Friction and wear properties of functionally graded aluminum matrix composites - Gomes, J. R.; Rocha, L. A.; Crnkovic, S. J. [UNESP]; Silva, R. F.; Miranda, A. S. (Trans Tech Publications, 2003)
Aluminum matrix composites are currently considered as promising materials for tribological applications in the automotive, aircraft and aerospace industries due to their great advantage of a high strength-to-weight ratio. A superior combination of surface and bulk mechanical properties can be attained if these composites are processed as functionally graded materials (FGM's). In this work, homogeneous aluminum based matrix composite, cast by gravity, and aluminum composites with functionally graded properties, obtained by centrifugal cast, are tested against nodular cast iron in a pin-on-disc tribometer. Three different volume fractions of SiC reinforcing particles in each FGM were considered in order to evaluate their friction and wear properties. The sliding experiments were conducted without lubrication, at room temperature, under a normal load of 5 N and constant sliding speed of 0.5 ms-1. The worn surfaces as well as the wear debris were characterized by SEM/EDS and by atomic force microscopy (AFM). The friction coefficient revealed a slightly decrease (from 0.60 to 0.50) when FGM's are involved in the contact instead of the homogeneous composite. Relatively low values of the wear coefficient were obtained for functionally graded aluminum matrix composites (≈10-6 mm3N-1 m-1), which exhibited superior wear resistance than the homogeneous composite and the opposing cast iron surface. Characterization of worn surfaces indicated that the combined effect of reinforcing particles as load bearing elements and the formation of protective adherent iron-rich tribolayers has a decisive role on the friction and wear properties of aluminum matrix composites.
Keywords: Aluminum matrix composites; Cast iron; Friction; Wear; Functionally graded aluminum matrix composites; High strength to weight ratio; Protective adherent iron rich tribolayers; Characterization; Functionally graded materials; Mechanical properties; Metallic matrix composites; Silicon carbide; Strength of materials; Surfaces; Tribology; Volume fraction; Wear of materials; Aluminum alloys